Gereja HKBP dalam Mempertahankan Identitas Kultural Diaspora Etnis Batak Toba di Kota Denpasar - Batee, Tony Hasudungan; Suwena, I Wayan; Sama, I Nyoman (Sunari Penjor : Journal of Anthropology; Vol 7 No 1 (2023): Volume 7. No. 1. Maret 2023, 2023)
Huria Kristen Batak Protestant (HKBP) is a Protestant Christian church in the Toba Batak ethinc group. HKBP cannot be separated from the life of the Toba Batak people. although basically the HKBP is a fellowship of Christians from all ethnic groups and groups. This study discusses the role of the church in an effort to maintain the cultural identity of the Toba Batak diaspora in Denpasar. and implications for both the congregation and the community around the church. This study uses the Functionalism Theory from Talcott Parsons and Symbolic Interaction Theory from Herbert Blumer. Qualitative research methods through data collection techniques in the form of observation, interviews, and documentation as well as using inductive data analysis techniques. Based on the results of the study, it was found that the Protestant Batak Christian Huria Church (HKBP) played a major role in maintaining the cultural identity of the Toba Batak diaspora in Denpasar. The implication of establishment of the Protestant Batak Christian Huria Church (HKBP) in Denpasar is the emergence of an exclusive and inclusive attitude from the congregation.